Game of thrones. The complete second season [videorecording (Blu-Ray)] - Caulfield, Bernadette; Benioff, David; Weiss, D. B.; Dinklage, Peter; Headey, Lena; Allen, Alfie, 1986-; Coster-Waldau, Nikolaj, 1970-; Clarke, Emilia, 1986-; Williams, Maisie, 1997-; Martin, George R. R. (Warner Home Video, 2013)
From the scheming south and the savage eastern lands, to the frozen north and the ancient wall that protects the realm from the mysterious darkness beyond, the powerful families of the Seven Kingdoms are locked in a battle for the Iron Throne.